PENYULUHAN KESEHATAN TENTANG TANDA-TANDA BAHAYA KEHAMILAN DI KLINIK PRATAMA TANJUNG - Haslin, Sharfina; Purba, Agnes Erna Taulina; Siregar, Ronni Naudur (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2023)
Danger signs in pregnancy are signs and symptoms encountered by pregnant women which are used as warning signs. Every woman needs to know and be aware of the signs and symptoms of danger in pregnancy, because complications are unpredictable. The purpose of counseling for this community is to increase the knowledge and insight of mothers regarding the signs of pregnancy through health education activities. The type of method used is to provide counseling about danger signs in pregnancy. The targets in this counseling activity were all pregnant women in Trimesters 1, 2 and 3. The participants involved were 15 people at the Tanjung Primary Clinic. This community service was carried out in December 2022. After being given material on danger signs of pregnancy, it was found that the number of pregnant women who had good knowledge was 14 people (93.3% and 1 person (6.7%) lacked knowledge. The conclusion from this community service was that A good effect was obtained from counseling on danger signs of pregnancy to pregnant women.